Vaginal versus abdominal hysterectomy in endometrial cancer: a retrospective study in a selective population. Issue 4 (1st July 2008) - Berretta, R.; Merisio, C.; Melpignano, M.; Rolla, M.; Ceccaroni, M.; De Ioris, A.; Patrelli, T. S.; Nardelli, G. B.
Abstract : The purpose of this study was to analyze the outcome of vaginal and abdominal hysterectomy for the treatment of early-stage endometrial cancer in a selected group of elder patients. This retrospective study analyzed a total of 154 patients: 113 (group I) underwent vaginal surgery and 41 (group II) underwent laparotomy. In both groups, we investigated the following parameters: intra- and postoperative complications, mean operative time, mean hospital stay, disease-free survival (DFS), overall survival (OS), and time of local or retroperitoneal recurrence. Medically compromised patients were significantly more frequent in the vaginal surgery group ( P = 0.005), and the operative duration in this group was significantly shorter ( P = 0.01). Intra- and postoperative complications, along with local and distant recurrence, did not show a statistically significant difference in the two groups. Total survival in the two populations, 85% at 5 years, did not reach statistically significant difference either in terms of DFS or in terms of OS. Vaginal surgery compared to traditional abdominal approach is feasible also in patients with high surgical risk; it does not require general anesthesia, abolishes abdominal trauma correlated to laparotomy, and allows a quicker reprise of the bladder and rectal function; therefore, it achieves high eradication rates and low intra- and postoperative morbidity rates.